PERMINTAAN TEMPE KOTA MALANG - Anasthasia Triwulan Budisaptorini (BiSTeK Pertanian, 2020)
Tempe is a processed soybean product whose nutritional value is increasing, especially protein (Hermana, 1985). Tempe is a typical Indonesian food that still survives to this day, even being a mainstay of Indonesian families because tempeh is rich in dietary fiber, calcium, vitamin B and iron. The purpose of this Research Purposes was to determine the characteristics of households that consume tempe and to determine the factors that influence the demand for tempeh in RW 02, Gading Kasri Village, Klojen District, Malang City. The analysis used in this study is multiple linear regression analysis because to determine the effect of each variable. The research variables are the price of tempeh, price, egg price, household budget to buy tempeh in a week, the number of household members. To find out the characteristics of households that consume tempe, descriptive analysis was carried out and to determine the effect of each variable, F test and t test were conducted. The results of the Fhitung analysis are 43,437> Ftable 2.33 or significant Fhitung 0.00 <0.05. Taken together to significantly influence the price of tempe (X1), the price of tofu (X2), the price of eggs (X3), the household budget (X4) and the number of household members (X5) on the demand for tempe (Y). the results of thitung analysis of the price variable tempe (X1) t -8,551> ttable 1,664, variable price (X2) thitung 0,428 <ttable 1,664, variable price of eggs (X3) thitung 1,182 <ttable 1,664, variable budget (X4) thitung 12,564 > ttable 1.664, variable number of household members (X5) thitung 3,534 > ttable 1.664. Shows that there is a real influence on the dependent variable